The Influence of Nutritional Education through Puppet Play to Increasing Vegetable and Fruit Consumption in Mekar Wangi and Putra Harapan Kindergarten Children Glenmore District - Murdani, Agus Putra; Nanda, Febrika Devi; laili, Nuris sa’datul (Journal for Quality in Public Health, 2021)
The consumption of vegetables and fruit is one indicator of nutritional balance. The statistical data show there are 60.44% of Indonesia that are less consuming vegetables and fruit. Fiber on vegetable and fruit are very useful for the body. Efforts to improve nutritional knowledge can preserve out through media which are suitable for children, that are attractive and easy to understand such as puppet and ladders game. This research aims to analyze the influence of the nutritional education through the game puppet to increase vegetable and fruit consumption for kindergarten children (TK). This is a pre-research experiment. One group pre-post test. Data analysis in this study uses the sample of this research is the Mekar Wangi and Putra Harapan kindergarten children that accounted 64 people in accordance. The technique of data collection from the questionnaire is based on the direct interviews, it aims to investigate the difference in vegetable consumption on kindergarten children before nutrition education is 5,58 while after nutrition is increase to 7,75. Whereas for fruit consumption for kindergarten children before education is 13,72 whereas after education is significantly increase to 16,47. The result revealed that there is an increment of education nitrition vegetable and fruit consumption after nutrition education through puppet game (Asymp.Sig =0,000) it concludes that nutritional education through puppet gameplay on an important role to increase the consumption of fruit and vegetables for kindergarten children.